Bentuk Respon Netizen terhadap UU Cipta Kerja pada Postingan tempodotco: Eufemisme dan Disfemisme - Vita Kusumaningtyas; Sulis Triyono (Balai Bahasa Sulawesi Selatan, 2023)
This study aims to describe the form of public responses in the tempodotco instragram post that contain euphemisms and dysphemism. This research is a descriptive-qualitative study. The data were collected by methods of reading-listening, note-taking and documentation techniques. The data were analyzed using the stages of data collection, data reduction, data presentation and conclusion of data. This research was the tempodotco instagram post with the headline